Adherence to a Mediterranean diet, lifestyle and age-related macular degeneration: the Coimbra Eye Study - report 3 - Raimundo, Miguel (2018)
Purpose To characterize the lifestyle and nutritional risk profile associated with the Mediterranean diet in a Portuguese population with and without age‐related macular degeneration (AMD). Methods Nested case–control study (n = 883) within the Coimbra Eye Study, including 434 subjects with AMD and 449 age‐ and sex‐matched subjects without AMD. All enrolled subjects underwent a full risk assessment, including lifestyle‐related risk factors and a thorough food frequency questionnaire. This allowed us to build an adherence score to the Mediterranean diet (mediSCORE, range 0–9) constructed from individual food intakes. Food intake was also further analysed by conversion to micronutrient consumption. Results Our results suggest that physical activity has a protective role in AMD [p = 0.018 after multivariate adjustment, OR: 0.69 (0.51–0.93)]. High (mediSCORE ≥6) was also found to be protective [p = 0.041, OR: 0.62 (95% CI: 0.38–0.97)]. Food group analysis unveiled a specific protective role for increased fruits consumption (p = 0.029). Finally, micronutrient analysis revealed a protective role associated with increased consumption of caffeine, fibres, beta‐carotene, vitamin C and vitamin E (p < 0.05). Conclusion High mediSCORE appears to confer protection against the development of AMD in a Mediterranean population. This effect is driven by increased consumption of fruits and some antioxidant micronutrients, which emerged as statistically significant protective factors. Further studies are required to establish dietary recommendations with clinical application.